2010
DOI: 10.1086/655229
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Microbial Translocation and Immune Activation in HIV‐1–Infected South Africans Receiving Combination Antiretroviral Therapy

Abstract: Microbial translocation is a major force driving chronic inflammation in HIV-infected Africans receiving cART. Prevention of monocyte activation may be especially effective at enhancing therapeutic outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
137
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(156 citation statements)
references
References 49 publications
16
137
1
2
Order By: Relevance
“…27,31,33 Our study results show that microbial translocation marker sCD14 was significantly elevated in the plasma from HIV-infected patients, consistent with previous studies. 45,46 Moreover, sCD14 showed significant correlation with HLA-DR 1 cd T cells.…”
Section: Chronic Immune Activation Depletes Memory Vd 2 CD T Cells Insupporting
confidence: 92%
See 1 more Smart Citation
“…27,31,33 Our study results show that microbial translocation marker sCD14 was significantly elevated in the plasma from HIV-infected patients, consistent with previous studies. 45,46 Moreover, sCD14 showed significant correlation with HLA-DR 1 cd T cells.…”
Section: Chronic Immune Activation Depletes Memory Vd 2 CD T Cells Insupporting
confidence: 92%
“…[31][32][33] LPS, a marker of microbial translocation, positively correlates with CD8 1 T-cell activation. 27 LBP is a serum glycoprotein that initiates an immune response after recognition of bacterial LPS in vivo.…”
Section: Microbial Translocation Contributes To Elevated Activation Omentioning
confidence: 99%
“…Analogously, Jiang et al showed that higher levels of DNA sequences encoding bacterial 16S rRNA genes are associated with greater T-cell activation and impaired CD4 ϩ T-cell restoration after ART (45). Similar data were also reported for a South African cohort, confirming persistently elevated LPS and sCD14 levels in INR despite virologically suppressive ART (62). While these findings provide important insights into the mechanisms determining the immunological response to ART, they still fail to formally prove that the level of microbial translocation is a key factor regulating CD4 ϩ T-cell reconstitution upon virologically suppressive ART.…”
Section: Clinical Implications Of Microbial Translocation In Hiv Disesupporting
confidence: 64%
“…Circulating levels of LPS have been consistently reported to decrease after the initiation of ART, even though they did not return to the levels observed for healthy HIV-uninfected individuals (33,39,45,62,65). Since persistent immune activation has long been implicated as a factor impairing the immunological response to ART (13,14), the question as to whether microbial translocation might affect immune recovery after ART has been investigated by different groups in the last few years.…”
Section: Clinical Implications Of Microbial Translocation In Hiv Disementioning
confidence: 99%
“…Activated CD14 + macrophages in necrotising enterocolitis produce nitric oxide (NO) that impairs endothelial repair [11,12]. We have shown that macrophages activation in HIV correlated with bacterial translocation and persistent immune activation [13].…”
Section: Introductionmentioning
confidence: 99%